2017
DOI: 10.1101/110809
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative insights to the transportome ofNosema: a genus of parasitic microsporidians

Abstract: Nosema, a genus of parasitic microsporidia, causes pebrine disease in arthropods, including economically important silkworms and honeybees. Nosema have gene-poor genomes shaped by loss of the metabolic pathways, as a consequence of continued dependence on host-derived substrates. As an act of counterbalance, they have developed an array of transporter proteins that allow stealing from their hosts. Here, we have identified the core set of twelve transporter families present in Nosema genus, viz. N. apis, N. bom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…We found that a number of genes thought to be involved in amino acid metabolism and procurement in yeast were upregulated by thermal stress in N. ceranae (Table S3). We found that two of the seven amino acid permeases (27) are upregulated by thermal stress (one of these, Aap [NCER_102107], is shown in Fig. 6A).…”
Section: Resultsmentioning
confidence: 99%
“…We found that a number of genes thought to be involved in amino acid metabolism and procurement in yeast were upregulated by thermal stress in N. ceranae (Table S3). We found that two of the seven amino acid permeases (27) are upregulated by thermal stress (one of these, Aap [NCER_102107], is shown in Fig. 6A).…”
Section: Resultsmentioning
confidence: 99%